Association of μ-Calpain and Calpastatin Polymorphisms with Meat Tenderness in a Brahman–Angus Population - Leal-Gutiérrez, Joel D.; Elzo, Mauricio A.; Johnson, Dwain D.; Scheffler, Tracy L.; Scheffler, Jason M.; Mateescu, Raluca G. (Frontiers in Genetics, 2018)
Autogenous proteolytic enzymes of the calpain family are implicated in myofibrillar protein degradation. As a result, the µ-calpain gene and its specific inhibitor, calpastatin, have been repeatedly investigated for their association with meat quality traits in cattle; however, no functional mutation has been identified for these two genes. The objectives of this study were: 1) to assess breed composition effect on tenderness; 2) to perform a linkage disequilibrium (LD) analysis in µ-calpain and calpastatin genes as well as an association analyses with tenderness; and 3) to analyze putative functional SNPs inside the significant LD block for an effect on tenderness. Tenderness measurements and genotypes for 16 SNPs in µ-calpain gene and 28 SNPs in calpastatin gene from 673 steers were analyzed. A bioinformatic analysis identified “putative functional SNPs” inside the associated LD block - polymorphisms able to produce a physical and/or chemical change in the DNA, mRNA or translated protein in-silico. Breed composition had a significant (P<0.0001) effect on tenderness where animals with more than 80% Angus composition had the most tender meat. One 11-kb LD-block and three LD-blocks of 37, 17 and 14 kb in length were identified in the µ-calpain and calpastatin genes, respectively. Out of these, the LD-block 3 in calpastatin, tagged by SNP located at 7-98566391 and 7-98581038, had a significant effect on tenderness with the TG-CG diplotype being approximately 1 kg more tender than the toughest haplotype, TG-CG. A total of 768 SNPs in the LD-block 3 of calpastatin were included in the bioinformatic analysis, and 28 markers were selected as putative functional SNPs inside the LD-block 3 of calpastatin; however, none of them were polymorphic in this population. Out of 15 initial polymorphisms segregating inside the LD-block 3 of calpastatin in this population, markers ARSUSMARC116, Cast5, rs730723459, and rs210861835 were found to be significantly associated with tenderness.